A research report on: Employment, job satisfaction and specialization preferences of registered Ayurveda doctors in Nepal: A descriptive cross-sectional study. - Bhandari,Sushant (2021)
EXECUTIVE SUMMARY: Constitution of Nepal and National Health Policy - 2019 A.D. provide guidance for utilization and regulation of Ayurveda and Alternative Medicine. People's attraction towards Ayurveda and Yoga is increasing day by day globally. Tribhuvan University and Nepal Sanskrit University are the only two universities running bachelor-level courses in the field of Ayurveda. Nepalese Ayurveda doctors are produced also from accredited institutions in India. Different Ayurveda professionals and the duties of Ayurveda Practitioners are regulated by "Nepal Ayurveda Medical Council (NAMC). In the context of the growing demand for Ayurveda practitioners, we want to explore how they are utilized, how their level of job satisfaction is, and what specializations they prefer (what kind of career they want to pursue).This study was a descriptive cross-sectional study in design, in which Ayurveda Doctors were selected randomly from the record of Nepal Ayurveda Medicine Council (NAMC) registration. A structured questionnaire was employed for selected the data collection after the consent. From the list of Ayurveda doctors obtained from the NAMC, we have included 201 registered Ayurveda doctors sequentially in descending order of registration number. Total population of registered Ayurveda doctors is 79885 in 95% confidence limit with margin of error: 6.5% and 50% likely sample proportion, desired sample size is 201. They were selected randomly using simple random sampling via computer-aided random selection process. 188 participants responded to the questionnaire with their consent and 13 provided non response replies. The responses were gathered from the participant via online Google form. Data was collected in Google sheet and was analyzed by the Statistical Program for Social Sciences (SPPS) version22.0. Total of 188 Ayurveda Doctors were assessed in the search through randomized sampling, showing ¼th of the Ayurveda population was unemployed. The average age is 38.11 and the average total duration of employment service in years is 8.946. This study shows that 1/4th of the Ayurveda practitioners are unemployed and 65% of the participants have not done a specialized degree. 2/3rd were satisfied with their current job. This study finds the need for higher specialization opportunities and the advancement of the working environment in the working areas of Ayurveda.